PEMBAYANGAN MATAHARI DAN PERHITUNGAN PEMBUKAAN DINDING DENGAN SOFTWARE AMETHYST SHADOW-FX - L.M.F Purwanto (Universitas Katolik Soegijapranata, 2022)
The buildings design in the tropics climate, shading on the walls is needed to prevent the entry of sunlight into the building. Shading is needed by determining the length of the sun shading and the placement of the height of the window, according to the orientation of the designed building. The purpose of this research is to determine the design of the building against the effort to block the entry of sunlight into the building with the simulation of Amethyst Shadow-FX software. The research method used is Ex Post Facto, where the independent variables are given treatment, namely variations in the shape and size of the wall opening and the orientation of the building. The results of this study are guidelines for designing building facades in the tropics and orientations that can produce thermal comfort in buildings because temperature increases can be avoided.